2016
DOI: 10.18632/oncotarget.10521
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA BC087858 induces non-T790M mutation acquired resistance to EGFR-TKIs by activating PI3K/AKT and MEK/ERK pathways and EMT in non-small-cell lung cancer

Abstract: Our previous study demonstrated that long non-coding RNA (lncRNA) BC087858 could stimulate acquired resistance to EGFR-TKIs in non-small cell lung (NSCLC) but the specific regulatory mechanism remained unknown. We aimed to explore the role and mechanism of lncRNA BC087858 on EGFR-TKIs acquired resistance. LncRNA BC087858 mRNA expression was detected by reverse transcription polymerase chain reaction in different NSCLC cell lines and tissues. The relationship between BC087858 expression and clinicopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 37 publications
6
53
0
Order By: Relevance
“…Moreover, our data revealed that Lasp2 promoted tumor invasion through upregulating Snail and downregulating Zo‐1. Either Snail or Zo‐1 was previously confirmed as EMT facilitator which was regulated by several signaling pathways including MAPK, PI3K‐AKT, and FAK, etc . In the present study, we found that overexpressing Lasp2 increased the phosphorylation of FAK in Tyr397 and Tyr925 but not AKT, ERK, and P38.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, our data revealed that Lasp2 promoted tumor invasion through upregulating Snail and downregulating Zo‐1. Either Snail or Zo‐1 was previously confirmed as EMT facilitator which was regulated by several signaling pathways including MAPK, PI3K‐AKT, and FAK, etc . In the present study, we found that overexpressing Lasp2 increased the phosphorylation of FAK in Tyr397 and Tyr925 but not AKT, ERK, and P38.…”
Section: Discussionsupporting
confidence: 61%
“…PI3K-AKT, and FAK, etc [27][28][29][30][31][32]. In the present study, we found that overexpressing Lasp2 increased the phosphorylation of FAK in Tyr397 and Tyr925 but not AKT, ERK, and P38.…”
supporting
confidence: 52%
“…CASC9 expression was upregulated in PC9G(pc-9gefitinib resistance) and knockdown of its expression increased the sensitivity of PC9G cells to gefitinib, while EWAST1(Linc00227) is downregulated in PC9G cells and overexpressed EWAST1 also leads to increased sensitivity of PC9G cells to gefitinib [103]. LncRNA BC087858 can promote cells invasion and induce non-T790M mutation acquired resistance to EGFR-TKIs by activating PI3K/AKT and MEK/ERK pathways and EMT via up-regulating ZEB1 and Snail in NSCLC [104]. Dong demonstrated that GAS5 can reduce tumor growth under treatment with gefitinib and IGF-1R is a key downstream mediator of GAS5 [105].…”
Section: Lncrnas In Lung Cancer Egfr Resistancementioning
confidence: 99%
“…There are also other lncRNAs with tumor suppressor or tumor promoting roles in lung cancer malignancies, like MEG3 (tumor suppressor), ANRIL, and AK001796 (oncogenic role) that are involved in cell proliferation and cell viability, processes that go hand in hand with the angiogenetic transformation [76][77][78]. lnRNA BC087858 is overexpressed in NSCLC and was demonstrated to be connected with drug resistance via EGFR-TKIs axis [80]. MEG3 was proved to be downregulated in tumoral tissue, and directly related with high tumoral stage.…”
Section: Lncrnas Related To Lung Cancer Angiogenesismentioning
confidence: 99%